Trade in services - market access opportunities and the benefit of liberalization for developing economies - Mc Guire, Greg (UN New YorkUS, 2002)
Provides an overview of international trade in services. Looks at market access and what is at stake for developing economies. Examines the restrictions and their effects. Highlights the importance of the financial services sector and focuses on unilateral and multilateral liberalization.